Spontaneous Intestinal Perforation in a Full Term Neonate: A Case Report - Dhungana, D.; Shrestha, R.; Ghimire, R.K.; Joshi, S. (Nepal Mediciti Medical Journal, 2022)
Spontaneous intestinal perforation suggests a perforation of the gastrointestinal tract of no demonstrable cause. Only few such cases have been described in full term newborns. Although some authors have suggested ischemia and fetal or neonatal hypoxia as the most likely cause, the etiology and pathogenesis of this disease are still widely unknown. Here, we present a case of Spontaneous intestinal perforation in a full term neonate who was born to a mother with chronic hypertension. Radiological images revealed pneumoperitoneum on a three day old baby with feeding intolerance and abdominal distention. There was no clinical evidence of Hirschsprung’s disease, necrotizing enterocolitis, anorectal malformations or bowel obstruction. An emergency laparotomy revealed a localized perforation in distal ileum. Histopathological examination failed to reveal any etiology for the perforation. The neonate recovered rapidly following a double barrel ileostomy, with no immediate gastrointestinal complications.